2014
DOI: 10.1378/chest.14-0735
|View full text |Cite
|
Sign up to set email alerts
|

Evacuation of the ICU

Abstract: BACKGROUND: Despite the high risk for patient harm during unanticipated ICU evacuations, critical care providers receive little to no training on how to perform safe and eff ective ICU evacuations. We reviewed the pertinent published literature and off er suggestions for the critical care provider regarding ICU evacuation. Th e suggestions in this article are important for all who are involved in pandemics or disasters with multiple critically ill or injured patients, including front-line clinicians, hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…While HMH’s response to the COVID-19 pandemic quickly paved the way for the full integration of the vICU with all its ICUs, more work is needed to improve preparedness for and resilience in future pandemics. In particular, frequent drills [ 12 ] and simulation training [ 13 ] have shown promise in preparing ICU staff for rare but high-consequence pandemic events. These efforts can focus on identifying necessary adjustments to staffing, layout, processes, and new use cases for vICU technology.…”
Section: Discussionmentioning
confidence: 99%
“…While HMH’s response to the COVID-19 pandemic quickly paved the way for the full integration of the vICU with all its ICUs, more work is needed to improve preparedness for and resilience in future pandemics. In particular, frequent drills [ 12 ] and simulation training [ 13 ] have shown promise in preparing ICU staff for rare but high-consequence pandemic events. These efforts can focus on identifying necessary adjustments to staffing, layout, processes, and new use cases for vICU technology.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that extreme emergencies, such as hurricanes and floods, might overwhelm a health-care facility’s ability to safely continue to care for patients, evacuation planning should be integrated into MCC emergency planning (see the “Evacuation of the ICU” article by King et al 30 in this consensus statement). 14,17,31,32 Hospitals are highly dependent on external infrastructure (eg, electricity, water, and communications) for basic functionality and patient safety, and backup systems have proven to be less than foolproof.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the aftermath of Hurricane Katrina (2005), approximately 45 patients are estimated to have died at a single hospital after hospital generators failed and patients were not evacuated to safety early enough. 6,33 Yet, evacuating medically complicated and fragile patients is complex and potentially dangerous to patients (see the “Evacuation of the ICU” article by King et al 30 in this consensus statement). 5 Contrasting the precautionary evacuations of hospitals in New York City before Hurricane Irene (2011) with the intraevent evacuations 1 year later during Hurricane Sandy (2012) demonstrates that a controlled, preplanned, collaborative evacuation may be safer than waiting to determine what to do in the midst of a disaster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of crowd simulation was already studied in different forms [ 69 , 70 , 71 ]. While there are multiple models to simulate the evacuation of people during hazards, such as wildfires [ 72 , 73 ], earthquakes [ 74 ], and tsunamis [ 75 ], very little research can be found that directly addresses this issue during a pandemic or epidemic [ 76 ]. Therefore, developing such multi-hazard evacuation models is a missing link towards overall community resilience.…”
Section: Multi-hazard Evacuation Modelsmentioning
confidence: 99%